Topoisomerase 3β knockout mice show transcriptional and behavioural impairments associated with neurogenesis and synaptic plasticity - Yuyoung Joo (Nature Portfolio, 2020)
Topoisomerase 3β (Top3β) solves topological stress in DNA or RNA metabolism and its mutations are linked to mental disorders. Here, the authors describe transcriptional and behavioural impairments in Top3β-knockout mice and show that these are linked to impaired neurogenesis and synaptic plasticity.